EFFECT OF INTERNAL VARIABLES OF SHARIA BANKS ON SHARIA BANKS PERFORMANCE - Akbar Ali; Syekh Syaid (Dinasti Publisher, 2019)
This research is to know the effect of internal variables of Sharia Banks (amount of financing and operational expense than operating income (BOPO)) on Sharia Banks Performance (Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Return On Asset (ROA) and Financing to Deposit Ratio (FDR) in Indonesia. The population in this research is the whole of Sharia Banks in Indonesia year of 2010 - 2017, with a sample of 6 Sharia Banks. The analysis tool uses Partial Least Square with SmartPLS program. The results of research showed that internal variables of Sharia Banks (amount of financing and BOPO) have a positive and significant effect on Sharia Banks Performance (CAR, NPF, ROA and FDR).